1995
DOI: 10.1596/0-8213-3516-2
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of a government targeted credit program

Abstract: Discussion Papers present results of country analysis or research that are circulated to encourge discussion and comment within the development community.To present these results with the least possible delay, the typescript of this paper has not been prepared in accordance with the procedures appropriate to formal printed texts, and the World Bank accepts no responsibility for errors. Some sources cited in this paper may be informal documents that are not readily available. The findings, interpretations, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 5 publications
0
21
0
1
Order By: Relevance
“…According to Khandker (1995) pervasive poverty affected millions of people in Bangladesh at many levels, and its alleviation required diverse measures. The most important interventions were those which provided employment and income generation opportunities to the rural poor, and enabled them enhance their living standards.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…According to Khandker (1995) pervasive poverty affected millions of people in Bangladesh at many levels, and its alleviation required diverse measures. The most important interventions were those which provided employment and income generation opportunities to the rural poor, and enabled them enhance their living standards.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Hulme and Mosley (1996) studied the improvement in income of 4,000 borrowers compared with control groups across four countries and concluded that microfinancing actually alleviates poverty. A number of social indicators, such as health and infant mortality, children's education, nutritional adequacy and attainment of food security, have been used to assess the performance of MFIs in other studies (see Foundation for Development Corporation, 1992;Pitt and Khandker, 1996;Khandker, Khan and Khalily, 1995;Khandker and Khalily, 1996;ADB, 2000;Dunford, 2001;CGAP, 2002). These studies have all confirmed that microfinancing helps to improve the income and quality of life of the poor.…”
Section: Performance Of Microfinancing Institutionsmentioning
confidence: 99%
“…Better road connection can reduce transaction costs of accessing credit and markets. Khandker et al (1995) noted that infrastructure and market connection determine the yields, farming productivity, and credit repayment by clients of Grameen Bank in Bangladesh. Similarly, Paxton (1996) asserted that better access to markets improves household credit repayment.…”
Section: After Matchingmentioning
confidence: 99%